2002
DOI: 10.1007/s00125-002-0856-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver glucokinase gene expression is controlled by the onecut transcription factor hepatocyte nuclear factor-6

Abstract: Aims/hypothesis. Glucokinase plays a key role in glucose homeostasis and the expression of its gene is differentially regulated in pancreatic beta cells and in the liver through distinct promoters. The factors that determine the tissue-specific expression of the glucokinase gene are not known. Putative binding sites for hepatocyte nuclear factor (HNF)-6, the prototype of the ONECUT family of transcription factors, are present in the hepatic promoter of the glucokinase gene and in diabetic hnf6 knockout mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We previously observed increased liver glycogen content in Oc1 heterozygous (OH) and DH mice at P21 because of Oc1 heterozygosity, in agreement with the role of Oc1 in hepatic glycogen breakdown (34,58,60). Thus, another possible explanation for the reduced blood glucose levels in DH at P14 was an increase in liver glycogen.…”
Section: Pdx1 and Oc1 Double Heterozygotes Show Normal Growth At P14supporting
confidence: 77%
See 1 more Smart Citation
“…We previously observed increased liver glycogen content in Oc1 heterozygous (OH) and DH mice at P21 because of Oc1 heterozygosity, in agreement with the role of Oc1 in hepatic glycogen breakdown (34,58,60). Thus, another possible explanation for the reduced blood glucose levels in DH at P14 was an increase in liver glycogen.…”
Section: Pdx1 and Oc1 Double Heterozygotes Show Normal Growth At P14supporting
confidence: 77%
“…6F). We had previously observed that DH mice had normal glucose tolerance at weaning likely because of increased liver glycogen content (26), which we hypothesized is the result of the known role of Oc1 regulation of genes involved in glycogenolysis in the liver (34,58,60). In looking at the livers from 3-mo-old animals, we observed that PH livers had reduced glycogen content compared with controls (Fig.…”
Section: E315mentioning
confidence: 67%
“…Null mice with global disruption of Hnf6 have aberrant hepatoblast maturation, abnormal bile duct formation and die early of cholestasis [3]. In the differentiated liver, Hnf6 regulates hepatocyte target genes involved in metabolic [4] [5] [6] and regenerative functions [7] [8]. We previously treated mice with recombinant human GH to increase in vivo Hnf6 expression and found that GH treatment improved bile duct ligation (BDL) hepatic injury, enhanced cholesterol clearance and improved hepatocyte-specific cellular proliferation [8].…”
Section: Introductionmentioning
confidence: 99%
“…PFKFB4 expression is regulated by the hepatocyte nuclear factor-6 (Hnf-6) [ 234 ] and diabetes developed in Hnf6-knockout mice [ 235 ]. PFKFB4 protein phosphorylation, mediated by the cAMP dependent protein kinase A (PKA) reduced F-2,6-P 2 level in the liver, thereby increasing gluconeogenesis with concomitantly reducing glycolysis [ 236 ].…”
Section: Heme Oxygenase Cadmium Cellular Stress Response and Defensementioning
confidence: 99%